Estimation of tree water stress from stem and soil water monitoring with timeâ€domain reflectometry in two small forested basins in Spain (Hydrological P, 2008)
Soil-tree water relationships were studied using time domain reﬂectometry (TDR) in two small forested basins in Spain. The stem water content of two Mediterranean Quercus species (Quercus pyrenaica and Quercus rotundifolia) was measured using previously constructed species-speciﬁc equations. To monitor soil moisture, a TDR station network was used in both cases. Sixteen Q. pyrenaica and six Q. rotundifolia individuals were selected to install two TDR probes in their trunks (at 20 and 120 cm above the ground) to monitor stem water content. Stem and soil water contents were measured fortnightly. The stem water content of both species showed a similar temporal trend for the period studied. A spring maximum (0Ð654 cm3 cm3 for Q. pyrenaica and 0Ð568 cm3 cm3 for Q. rotundifolia) was found to be associated with high transpiration and no soil moisture deﬁcit, and a late-summer minimum (0Ð520 cm3 cm3 for Q. pyrenaica and 0Ð426 cm3 cm3 for Q. rotundifolia) was associated with the end of the dry season. This drop in stem water content occurs when the available water in the soil decreases. This seasonal difference presumably reﬂects water withdrawn from stem storage to support the transpirational demands of the tree. Since plant water stress results in reduced stem water content and since this drop can be measured by TDR, it may be concluded that this technology offers a suitable tool for detecting plant water stress